The Caregiving Health Engagement Scale (CHE-s): development and initial validation of a new questionnaire for measuring family caregiver engagement in healthcare - Serena Barello; Cinzia Castiglioni; Andrea Bonanomi; Guendalina Graffigna (BMC, 2019)
Abstract Background This study was aimed to preliminary validate a cross-disease psychometric measure to assess the psycho-social experience of family caregiver engagement in healthcare (Caregiving Health Engagement Scale, CHE-s), which refers to the caregiver's psychological attitude to be an active, skilled and motivated player in the care process of their loved ones. Method The study consisted of a mixed methods, multi-stage research. First, a preliminary qualitative stage was aimed at investigating - in the caregivers' perspective - the engagement process in providing care to a ill relative (stage 1). The second stage of the research was aimed at developing a psychometric scale to assess this concept (i.e. the Caregiving Health Engagement Scale - CHE-s) and to preliminary test its psychometric properties (stage 2). Results Overall, 230 caregivers (32 in stage 1, and 198 in stage 2) participated to the study. The first qualitative stage, conducted by qualitative interviews on 32 family caregivers, highlighted four main experiential positions of caregiver engagement (namely, denial, hyper-activation, drawing, and balance), showing that "full engagement" occurs when caregivers become able to reach balance between their caring tasks and their broad life goals. In the second quantitative stage, we used the qualitative evidences emerged from stage one as a basis for developing the items of the Caregiving Health Engagement scale (CHE-s). We preliminary tested its psychometric properties through a cross-sectional study on 198 caregivers, which demonstrated CHE-s to be a reliable measure to capture the dynamic nature of caregiver engagement. The CATPCA results, together with the ordinal alpha of 0.88, suggests a mono-dimensional latent structure and a very good internal consistency and CFA showed adequate goodness of fit indices. (CFI = 0.96, RMR = 0.03, RMSEA = 0.05). Conclusions Health care systems that prioritize person-led care may benefit from using the Caregiving Health Engagement Model and the CHE scale (CHE-s) to assess the engagement level of family caregivers in order to better tailor the supportive and educational intervention addressing them.